A Case of Rapidly Progressing Hepatocellular Carcinoma after Administration of JAK Inhibitors to Treat Rheumatoid Arthritis. (29th March 2022) - Migita, Rioko; Kimoto, Yasutaka; Hiura, Junki; Okumura, Yuta; Horiuchi, Takahiko
Abstract : We report a case of rapidly progressing hepatocellular carcinoma after administration of Janus kinase (JAK) inhibitors to treat rheumatoid arthritis. A 76-year-old man was referred to our Department for pain in multiple joints and was diagnosed with rheumatoid arthritis. Blood tests revealed elevated hepatobiliary enzymes, but various tests revealed no signs suggestive of malignancy. He took baricitinib for 2 months followed by tofacitinib for 4 months. After that, he was diagnosed with hepatocellular carcinoma based on imaging findings and elevated tumor markers. This case showed the possibility of a causal relationship between JAK inhibitors and malignancy.